Selection of Robot for Contour Crafting Using Analytical Hierarchy Process - Shanmugasundaram, Senthilraja; Murugan Chidhembaram, Raja Muthaiah (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The use of robotic equipment and a new technique called contour crafting allows for the construction of buildings at lower labor and material costs. The selection of the type of robot is an important factor that affects the overall performance of the contour crafting (CC) system. Various robot configurations, such as gantry, cylindrical, and SCARA, may be employed for contour crafting. There are benefits and drawbacks to using different types of robots for various tasks, including cost, work volume, material compatibility, and precision.
Keywords: multi criteria decision making (MCDM); contour crafting; analytical hierarchy process (AHP)